(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to develop an educational video on preventing child marriage, assess the feasibility of the media, and test its effectiveness in improving students’ knowledge. The study used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The media effectiveness test used a one-group pretest-posttest design on 86 students of grades VIII and IX of UPTD SMP Negeri 2 Bola selected using a total sampling technique. Data were collected through a needs analysis questionnaire, expert validation sheets, pretest-posttest knowledge tests, interviews, and evaluation questionnaires. Data were analyzed descriptively, while media effectiveness was analyzed using a Paired Sample t-test. The results showed that the educational video obtained a very feasible category based on expert assessment with a feasibility level of 96.5% for the material aspect and an average of 86.5% for the media aspect. The average student knowledge score increased from 3.51 in the pretest to 4.43 in the posttest, and the results of the Paired Sample t-test showed a significant difference (p=0.001). These findings indicate that the educational video developed not only meets the eligibility criteria but also contributes to increasing students’ knowledge about preventing child marriage. This medium has the potential to be used as an alternative educational tool in schools to support child marriage prevention efforts